Teacher’s and Student’s Vocabulary Strategies in A Remote EFL Classroom: Story from Central Borneo Indonesia - Dara, Sari Wulan; margana, Margana (Intensive Journal, 2025)
The purpose of this study is to explore the strategies used by both teacher and students for enhancing vocabulary in junior high school, especially in a remote area with limited resources. The research focus on the strategies used by teachers and students in vocabulary retention and provide insights into the effectiveness of various teaching and learning strategies in remote area. A qualitative descriptive approach was employed, with data collected through interviews, classroom observation and document analysis. The findings suggested that both teachers and students devised innovative strategy to overcome challenges of teaching vocabulary with limited resources environment, such as using visual aids, gestures, and contextual guessing. The study also emphasized the importance of creative strategies, given the scarcity of digital resources and exposure to English outside classroom.